Cell immunity at pregnant women with autoimmune thyroiditis and gestosis - A. Sh. Makhmuthodzhayev; L. M. Ogorodova; I. D. Evtushenko; A. V. Holopov; E. L. Timoshina; E. V. Makhmuthodzhayeva (Бюллетень сибирской медицины)
In a prospective study the group of 60 women with AIT and thyroidological uneventful control women, matched for age and parity (n = 30) were tested at 12 and 32 weeks gestation for percentages of peripheral blood lymphocyte subsets (CD3, CD4, CD8, CD16, HLA-DR major histocompatibility complex (MHC)-class II), IL-2, IFN-gamma, TPO-Abs, TSH and thyroxin. Twenty five pregnant women with AIT (41,7%) developed preeclampsia (against 16,7% in control). Pregnancyrelated CMI alterations consisted of low percentages of CD16+ NK cells and all subpopulations of T-cells at 12 weeks gestation. The development of preeclampsia in women with AIT was accompanied with increasing percentage of HLADR+ T- lymphocytes. The high levels of TPO-Abs and activated T-lymphocytes in pregnant women with autoimmune thyroiditis has been suggested as a predictor for later preeclampsia development.